Allergenicity and Conformational Diversity of Allergens - Clarissa A. Seidler; Ricarda Zeindl; Monica L. Fernández-Quintero; Martin Tollinger; Klaus R. Liedl (Allergies, 2024)
Allergens are substances that cause abnormal immune responses and can originate from various sources. IgE-mediated allergies are one of the most common and severe types of allergies, affecting more than 20% of the population in Western countries. Allergens can be subdivided into a limited number of families based on their structure, but this does not necessarily indicate the origin or the route of administration of the allergen, nor is the molecular basis of allergenicity clearly understood. This review examines how understanding the allergenicity of proteins involves their structural characterization and elucidates the study of conformational diversity by nuclear magnetic resonance spectroscopy. This article also discusses allergen cross-reactivity and the mechanisms by which IgE antibodies recognize and bind to allergens based on their conformational and linear epitopes. In addition, we outline how the pH, the proteolytic susceptibility and the endosomal degradation affect the outcome of allergic reactions, and how this is correlated with conformational changes and secondary structure rearrangement events. We want to emphasize the importance of considering structural diversity and dynamics, proteolytic susceptibility and pH-dependent factors to fully comprehend allergenicity.